Mifepristone versus Dienogest in Medical Management of Endometrioma Up to 6 Cm Diameter: A Prospective Observational Study - Bansi Bisal; Bansi Bisal; Shyamali Dutta; Palash Mazumder; Tarasankar Bag, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Endometriosis, the presence of endometrial tissue outside the uterus, is a chronic estrogen-dependent condition affecting ~10% of reproductive-age women, peaking at 25–30 years. It accounts for ~60% of pelvic pain and 50% of infertility cases. Lesions may occur on pelvic peritoneum, ovaries, recto vaginal septum, ureter, and rarely elsewhere. Ovarian endometriosis, often associated with endometriomas (55% of cases), can cause adhesion and symptoms such as dysmenorrhea, premenstrual pain, dyspareunia, and fatigue. Objective: To compare Dienogest and Mifepristone in reducing pain and endometrioma .size in endometriosis. Materials & Methods: This randomized clinical trial was conducted in the G&O OPD, Medical College Kolkata (June 2020–May 2021). Women with dysmenorrhea, diagnosed with endometrioma ≤6 cm, and not seeking conception were included. Those with severe pain needing hospitalization or requiring surgery were excluded. A total of 236 patients were randomized equally: Group 1 received Dienogest 2 mg/day; Group 2, Mifepristone 25 mg/day. Follow-up at 3 and 6 months assessed endometrioma size and pain using the Visual Analogue Scale (VAS). Results: Reduction in endometrioma size showed no statistical significance between groups at 3 or 6 months (p=0.2024, p=0.0522). Pain reduction at 3 months was greater with Dienogest (VAS 3.92±1.65) vs Mifepristone (4.69±1.45), p<0.0001. At 6 months, scores further declined (0.53±0.64 vs 0.82±0.71), p=0.0012. Overall pain reduction was greater with Dienogest (8.10±0.99 vs 7.82±1.03), p=0.0342. Conclusion: Dienogest was more effective than Mifepristone in relieving endometriosis-associated pain, with no significant difference in endometrioma size reduction.